สัปปุริสธรรม: หลักธรรมเพื่อการสงเคราะห์ Sappurisa Dhamma: The Principle of Public Service - ชั้นไพบูลย์, อุดมพร (วารสารรามคำแหง ฉบับมนุษยศาสตร์, 2014)
บทคัดย่อ ตามหลักคำสอนในพระพุทธศาสนา ผู้ที่สามารถให้ความช่วยเหลือ แนะนำ ชี้ช่องทางการปฏิบัติเพื่อดับทุกข์หรือขจัดปัญหาของชีวิตให้แก่บุคคลอื่นได้ต้องเป็นผู้มีคุณธรรม ๗ ประการ คือ สัปปุริสธรรม ๗ ซึ่งประกอบด้วย ธัมมัญญุตา ความรู้จักธรรม อัตถัญญุตา ความรู้จักอรรถ อัตตัญญุตา ความรู้จักตน มัตตัญญุตา ความรู้จักประมาณ กาลัญญุตา ความรู้จักกาล ปริสัญญุตา ความรู้จักบริษัทหรือชุมชน และปุคคลปโรปรัญญุตา ความรู้จักบุคคล ที่นักสังคมสงเคราะห์ควรปลูกฝังให้มีขึ้น เพื่อการมีสัมพันธภาพกับผู้รับบริการอย่างราบรื่น และนำไปสู่การป้องกันปัญหา แก้ไขปัญหา ฟื้นฟู และพัฒนาชีวิตให้ดีขึ้นแก่บุคคล กลุ่ม ชุมชน ตามจุดมุ่งหมายของการสังคมสงเคราะห์ Abstract According to Buddhism, one who qualifies to provide either an assistance, recommendation or advice to the others in order to prevent and rescue them from the state of sufferings or dilemmas must be fulfilled with the seven virtuous qualities of a good man or Sappurisa Dhamma. They are (1) Dhammannuta, the knowing of causes underlying all the happenings, (2) Atthannuta, the knowing of the results or fruition derived from the causes, (3) Attannuta, the knowing of one’s own self or self-knowledge, (4) Mattannuta, the knowing of moderation or the sense of proportion, (5) Kalannuta, the knowing of time or time management, (6) Parisannuta, the knowing of the populated communities or societies or even the assembly, and (7) Puggalannuta, the knowing of an individual, or in other words, the individual differences. It is a ‘must’ for the social workers to be imbued or implanted with those seven virtuous qualities, due to which they will be able to create good understanding of, and good relationship with, the residents of the communities or societies. As a result, it will be conducive to the effective preventive as well as curative measures and solutions in the process of rendering rescue and development activities for the betterment of the populated communities or societies as the main objective of the social works.